2016
DOI: 10.2525/ecb.54.57
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric Quantification of Ferulic Acid Concentrations Based on Deconvolution of Intrinsic Fluorescence Spectra

Abstract: Ferulic acid (FA) is one of phenolics found in most higher plants. It is important to quantify the internal FA level in vegetables and fruits, since it was epidemiologically demonstrated and a number of study supported that consumption of fruits and vegetables rich in phenolic acids including FA is associated with the prevention of chronic diseases such as cancer and cardiovascular disease. In order to allow handling of the intact fresh produces, non-invasive methods are desired. Previously, 355 nm ultraviolet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Epicatechin belongs to the proanthocyanidins of condensed tannins in flavonoids, is found in the cell wall (Serrano et al., 2009), and has strong antioxidant activity by scavenging free radicals (Fraga et al., 2018). In addition, the embryophyte cell wall complex is rich in water‐insoluble ferulic acid, which is cross‐linked with the cell wall matrix by esterification (Inokuchi et al., 2016; Tiessen, 2018). The content of ferulic acid increased during the thermal treatment, indicating that ferulic acid changed from a bound form to a free form.…”
Section: Resultsmentioning
confidence: 99%
“…Epicatechin belongs to the proanthocyanidins of condensed tannins in flavonoids, is found in the cell wall (Serrano et al., 2009), and has strong antioxidant activity by scavenging free radicals (Fraga et al., 2018). In addition, the embryophyte cell wall complex is rich in water‐insoluble ferulic acid, which is cross‐linked with the cell wall matrix by esterification (Inokuchi et al., 2016; Tiessen, 2018). The content of ferulic acid increased during the thermal treatment, indicating that ferulic acid changed from a bound form to a free form.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we postulated that at least in the case of the F3a,b, and F4a, b fibers, some of the drug content might be present on the surface of the fibers. To probe this, we exploited the fact that FA was known to show bluegreen fluorescence (Inokuchi et al, 2016). Fluorescence microscopy images of the fibers (Figure 14) were recorded, and it was observed that intense fluorescence was visible at the exterior of the fibers.…”
Section: Drug Release Studymentioning
confidence: 99%